Effect of Competency and Workload on Work Stress on Employees of PT. Pramadani Cipta Kreasi Kab. Cirebon - Rahayu Tri Utami; Susilo Wulandari; Sandi Nasrudin Wibowo; Liyanah (Quantitative Economics and Management Studies, 2022)
This study aims to determine the effect of Competence and Workload on Work Stress at PT. Pramadani Cipta Kreasi Kab. Cirebon. The research method used is quantitative research methods. The population in this study were employees of PT. Pramadani Cipta Kreasi Kab. Cirebon. The technique used in sampling is saturated sample, where the total population is used as a sample of 52 respondents. The method of collecting data is using a questionnaire, while the method in this study uses multiple linear regression analysis. The results of this study indicate that competence has no significant effect on work stress as seen from tcount < ttable that is -1.957 < 2.00856, Workload has a significant effect on work stress seen from tcount > ttable which is 3.126 > 2.00856 and simultaneously Competence and Workload have a positive and positive effect. significant effect on work stress is shown by Fcount > Ftable which is 6.473 > Ftable of 3.19. From the partial results, Competence has a sig value of 0.000 and Workload has a sig value of 0.000, and the simultaneous results have a sig <0.05 or 0.000 <0.05.